CHANGES IN JOINT SPACE WIDTH ONE YEAR AFTER WEIGHT LOSS SURGERY - Vuononvirta, L.T.; Turmezei, T.D.; Frondelius, T.J.; Nevalainen, M.T.; Rytky, S.J.O.; Määttä, J.H.; Meriläinen, S.A.; Lehenkari, P.P.; Finnilä, M.A.J. (Osteoarthritis imaging, 2025)
Weight loss—either conservative or surgical—can slow OA progression. Traditional radiography has limited sensitivity in detecting early or subtle joint changes induced either by OA or weight loss. The limitations of conventional radiography can be alleviated by using CT. Weight-bearing cone-beam CT -imaging can be used to detect the OA induced changes in JSW. These changes can be evaluated by using joint space mapping (JSM), a novel CT-based technique, which enables quantitative 3D assessment of JSW with high spatial resolution. To assess longitudinal changes in left knee joint space width following Roux-en-Y gastric bypass (RYGB) surgery using weight-bearing cone-beam CT, expecting that substantial weight loss would be associated with joint space widening. This one-year longitudinal study included 86 morbidly obese subjects (72 F, 14 M), of whom 45 underwent RYGB surgery and 41 served as a control group following conservative weight loss. Subgroup analyses were stratified by weight loss success. Unilateral weight-bearing cone-beam CT scans of the left knee in full extension were acquired at baseline and 1-year follow-up using Planmed Verity (voxel size: 0.2 mm³; 801 × 801 × 651; 96 kVp, 12 mA). Images were processed in DICOM format. JSM was performed using Stradview (v7.21) for segmentation and measurement of JSW, and WxRegSurf (v23) for co-registration to a canonical surface. Subregions were manually defined based on standard tibial cartilage thickness maps. Statistical parametric mapping (SPM) was conducted using MATLAB (2022) and SurfStat. Group differences in subregional mean JSW changes were assessed using two-sample t-tests. In the control group, BMI change was 0.0 ± 5.8 kg/m². RYGB patients with successful weight loss (≥20% BMI reduction) showed a mean BMI change of −11.2 ± 8.4 kg/m², while the unsuccessful subgroup had a change of −5.7 ± 8.1 kg/m². Regarding JSW, both surgical subgroups exhibited a general trend toward joint space redistribution in the knee (Figure 1). However, subregional analysis revealed significant JSW widening (p < 0.05) in the successful group, particularly in the central region (+0.13 ± 0.05 mm) and the medial quarter (+0.22 ± 0.23 mm) of the medial tibiofemoral compartment (Figure 2). Non-significant narrowing was seen anteriorly in the lateral compartment along with posterior widening. This study demonstrates that successful weight loss following RYGB surgery is associated with significant region-specific increases in JSW in the medial compartment of the knee at a one-year interval, specifically in the central and inner regions of the medial tibiofemoral compartment. These findings suggest that weight reduction may lead to unloading of joint structures, especially at the medial compartment, which may alleviate cartilage compression and meniscal extrusion.